EFFECT OF MEPIQUAT CHLORIDE AND POTASSIUM SOURCES ON GROWTH AND YIELD OF PATATO PLANTS (SOLANUM TUBEROSUM L.) - Ali Abo Al-Nagaa (Arab Universities Journal of Agricultural Sciences, 2019)
In this study, Two field experiments were conducted in Ourabi operation Farm, Cairo-Ismaellia desert road at Kalubia Governorate. The experiment was carried out during the two seasons of  2013/2014 and 2015/2016, to investigate the effect of  plant growth regulator (Mepiquat chloride) with three different potassium fertilizers sources [chemical potassium (KC), foliar potassium (KF) and rock potassium (KR)] on growth development and total yield in potato plants (Solanum tuberosum L. cv. Spunta) . Chemical potassium (control) with / without Mepiquat chloride achieved better plant height, no. of stem and leaf area/plant. Rock potassium with mepiquat chloride  obtained the highest productivity of fresh and dry weights, total tuber yield and yield components  (weight of tubers, size of tubers, diameter of tubers and number of tubers) following by foliar potassium with mepiquat chloride  compared with control treatment.